Penggunaan Google Drive untuk Laporan Bumdes Tunan Desa Talawaan Kec. Talawaan Kab. Minahasa Utara - Heidy Pesik; Fresi Beatrix Lendo; Sintya Junaedy (Syntax Corporation Indonesia, 2024)
This study discusses the use of Google Drive in the context of preparing Bumdes reports in Talawaan Village, Talawaan District, North Minahasa Regency. The main objective of this study was to evaluate the impact of Google Drive implementation on efficiency, collaboration, and transparency in Bumdes' report management process. Through data analysis and case studies, the research reveals that using Google Drive provides ease of access, facilitates real-time team collaboration, and improves document security and version management. In addition, administrative efficiency is also seen to increase, with reduced reliance on physicala dministration. The use of Google Drive also provides a higher level of transparency in the presentation of Bumdes reports to related parties and the public. The results of this study provide a positive outlook on the implementation of Google Drive as a comprehensive and effective management tool in the context of Bumdes, with potential implications for improved performance and adaptation to changes at the village level.